A contribuição da prosódia e da qualidade de voz na expressão de atitudes do locutor em atos de fala diretivos - Horacio dos Santos Queiroz (2011)
The aim of this thesis is to investigate the way in which prosody and paralinguistic features of voice quality may contribute to the expression of speakers attitude in three different types of speech acts with the same directive illocutionary point but different illocutionary forces: requests, supplications, and orders. The prosodic level of analyses was based mainly on the behavior of fundamental frequency (f0) and duration. The acoustic correlates of voice quality includes spectral amplitudes of the first and the second harmonics (H1/ H2), and the acoustic measurements of A1, A2 e A3, which are correlated to different types of phonation: modal voice, breathy voice and creaky/fry voice, which were analyzed in this work. At the pragmatic level, the theoretical and methodological principles of Speech Acts Theory were explored; the descriptive interpretation of prosodic characteristics were related to thedirective speech acts, to the notion of illocutionary force, and to the six types of operations on illocutionary forces, which consists in changing the components of these forces in some way. The results demonstrate that prosodic and paralinguistic information can be related to specificspeech acts (modal function), allowing as well the evaluation and the description of subclasses of requests, supplications and orders, which can be related to differences at the prosodic level (e.g. f0 contour, duration and register), and differences at the paralinguistic level (e.g. spectral characteristics), both contributing to the effective mode of achievement of illocutionary points, revealing that prosody and voice quality are essential to the effective interpretation of illocutionary acts.In addition, the results show that different prosodic and paralinguistic strategies can differ not only with respect to the mode of achievement but also with respect to the speakers attitude (attitudinal function), that is, both strategies are essential elements of the speakers communicative intentions which can be analyzed, on the one hand, by the nature of prosodic information and, on the other hand, by the illocutionary logic which includes syntactic, semantic and pragmatic levels, allowing the investigation and the description of possible contingent and specific relations between prosody and speakers attitude.